Deriving Poverty Lines of Manipur State using Consumer Price Indices (International Journal of Food and Nutritional Sciences, 2023)
The main objective of this present paper is to estimate poverty line for the State of Manipur using the methodologies developed by the Tendulkar Committee and Rangarajan. Poverty lines for Manipur are derived by updating poverty lines from 2011-12 to 2018-19 using Consumer Price Indices for urban and rural Manipur. Data of the current study is based on primary and secondary sources. It also used data from the report of the estimation of poverty in Manipur (2019). The present study has recommended three sets of poverty lines for Manipur, namely (i) Rs 1442.6 for all Manipur, (ii) Rs 1442.6 for all urban areas of Manipur and Rs. 1700.6 for all rural areas of Manipur and (iii) Rs 1442.6 for all urban areas of Manipur and Rs. 1716.2 for all rural areas of Manipur. This is not surprising because Manipur is relatively a small State and there is connectivity among the district through relatively good transport system. Therefore, the prices between rural and urban areas and between districts did not differ significantly.